Scientific Method Skills of Prospective Teacher Students Based on Their Major Background Science and Non-Science - Fatmawati, Baiq (Sumber Belajar Sejahtera, 2025)
The systematic method of acquiring knowledge based on physical evidence is known as the scientific method. It is also one of the main goals of science education, aiming to evaluate one's ability to solve problems and generate new knowledge systematically. This study aims to analyze differences in scientific method skills between prospective teacher students from science and non-science backgrounds, and to explore the correlations between scientific thinking components. Of the 102 potential teachers from Hamzanwadi University who participated in the study, 58 had a background in science and 44 did not. In order to represent the variety of educational streams enrolling in teacher education programs, participants were chosen based on their high school academic performance. Pearson correlation analysis and an independent samples t-test were used to analysis data. The results showed that science students performed better in the question and procedure components. However, there were no significant differences in problem identification, hypothesis, prediction, and conclusion components. Correlation analysis revealed that science-background students displayed more systematic and logical thinking patterns, with strong correlations among scientific thinking stages. Conversely, non-science students exhibited weaker and inconsistent relationships among components, especially in the initial stages of the scientific process. Systematic and contextual science learning must be strengthened using differentiated approaches based on students’ educational backgrounds. These results have significant implications for developing curricula that enhance scientific thinking skills across disciplines.